Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Is the following inequality in a triangle known? $$4(\cos A + \cos B + \cos C) \le 3 + \cos \left(\frac{B-C}{2}\right) + \cos \left(\frac{C-A}{2}\right) + \cos \left(\frac{A-B}{2}\right)$$ It looks correct to me but I would appreciate if someone confirm it.

share|improve this question
    
It's not correct. Let $a=0, b=\pi/2, c=1$ –  i. m. soloveichik Jul 24 '12 at 2:21
1  
The assumption is that $A+B+C = \pi$, i.e. $A,B,C$ are angles in a triangle. –  Martin Jul 24 '12 at 5:15
1  
Evaluating the inequality with Mathematica with brute force, for $0<B<\pi/2$, $B\leq A<\pi-B$ and $C=\pi-A-B$ and with a grid of tickness $\pi/1000$, it seems to be true, but I have no proof. Moreover, every relaxation on the coefficients (4.1 instead of 4, or 2.9 instead of 3) invalidates the inequality. –  enzotib Jul 24 '12 at 16:16
    
Thank you enzotib. Your mathematical experiment gives strong enough evidence. It appears to be difficult to prove the inequality rigorously. –  Martin Jul 24 '12 at 18:49
1  
The inequality is strict at $A=B=C=\pi/3$ and permutations of $A=B=0, C=\pi$, so relaxation of the coefficients is definitely not possible. –  Rahul Jul 25 '12 at 12:09
show 1 more comment

3 Answers

$\cos A+\cos B+\cos C=2\cos\frac{A+B}{2}\cos\frac{A-B}{2}+1-2\sin^2\frac{C}{2}$

$=2\sin\frac{C}{2}\cos\frac{A-B}{2}+1-2\sin^2\frac{C}{2}\quad$ as $\quad A+B+C=\pi$ $\implies\cos\frac{A+B}{2}=\sin\frac{C}{2}$

$\leq 2\sin\frac{C}{2}+1-2\sin^2\frac{C}{2}\quad$ as $\quad\cos\frac{A-B}{2}\leq 1$

$=-\frac{1}{2}(2\sin\frac{C}{2}-1)^2+1+\frac{1}{2}$

The maximum value will come if $2\sin\frac{C}{2}=1\quad$ and if $\quad\cos\frac{A-B}{2}=1$

or if $\quad C=\frac{\pi}{3}\quad$ and $\quad A=B$. Then $A+B=\frac{2\pi}{3}\implies A=B=\frac{\pi}{3}=C$

The maximum value of $\cos A+\cos B+\cos C\quad$ thus $\quad\frac{3}{2}$

(i)Now, $4(\cos A+\cos B+\cos C)=2(\cos A+\cos B+\cos C)+2(\cos A+\cos B+\cos C)$

$\leq 2(\cos A+\cos B+\cos C)+2.\frac{3}{2}$

$=3+(\cos A+\cos B)+(\cos B+\cos C)+(\cos C+\cos A)$

Now, $\cos A+\cos B=2\cos\frac{A+B}{2}\cos\frac{A-B}{2}=2\sin\frac{C}{2}\cos\frac{A-B}{2}$

So, the problem reduces to $\sum 2\sin\frac{C}{2}\cos\frac{A-B}{2}≤ \sum \cos\frac{A-B}{2}$

(ii) Now, $4(\cos A+\cos B+\cos C)=(\cos A+\cos B+\cos C)+3(\cos A+\cos B+\cos C)$

$\leq (\cos A+\cos B+\cos C)+3.\frac{3}{2}$

$=3+\frac{1}{2}\sum (\cos A+\cos B + 1)$

$=3+\frac{1}{2}\sum (2\sin\frac{C}{2}\cos\frac{A-B}{2} + 1)$

So, the problem reduces to $\sum( \sin\frac{C}{2}\cos\frac{A-B}{2} + \frac{1}{2}) ≤ \sum \cos\frac{A-B}{2} $

I'm trying to prove this.

share|improve this answer
add comment

Excuse me if what I'm going to tell is too imprecise but an approach that might work is the following: define $x_1=\cos\frac{A}{2},x_2=\sin\frac{A}{2}$ and similarly $x_3,x_4$ for $B$ and $x_5,x_6$ for $C$. Using the formulas for the sine and cosine of the sum of two angles the inequality we want to prove is (if I didn't mess anything up) $$ 4(x_1^2-x_2^2+x_3^2-x_4^2+x_5^2-x_6^2)\leq 3+x_1x_3+x_2x_4+x_1x_5+x_2x_6+x_3x_5+x_4x_6. $$ Consider then the function $f:\mathbb{R}^6\rightarrow\mathbb{R}$ defined by $$ f(x_1,\ldots,x_6)=4(x_1^2-x_2^2+x_3^2-x_4^2+x_5^2-x_6^2)-(x_1x_3+x_2x_4+x_1x_5+x_2x_6+x_3x_5+x_4x_6). $$ We want to maximise it with the constraint given by $A+B+C=\pi$, which can be expressed in terms of the $x_i$, although not uniquely I'm afraid. Then we could make use of Lagrange multipliers.

Also $f$ is obviously a homogeneous degree 2 polynomial, so it defines a (projective) quadric. I wonder if this might be of help.

EDIT: The constraints $\cos(A+B+C)=-1$ and $\sin(A+B+C)=0$ in terms of the $x_i$ are $$ (x_1^2-x_2^2)(x_2^2-x_3^2)(x_5^2-x_6^2)-4(x_1^2-x_2^2)x_3x_4x_5x_6-4x_1x_2(x_3^2-x_4^2)x_5x_6-4x_1x_2x_3x_4(x_5^2-x_6^2)=-1 $$ and $$ 2x_1x_2(x_3^2-x_4^2)(x_5^2-x_6^2)+2(x_1^2-x_2^2)x_3x_4(x_5^2-x_6^2)+2(x_1^2-x_2^2)(x_3^2-x_4^2)x_5x_6-8x_1x_2x_3x_4x_5x_6=0. $$ Note that this only tells us that $A+B+C$ is an odd multiple of $\pi$ and not exactly $\pi$.

share|improve this answer
    
The costraints $x_1^2+x_2^2=1$ and similar need not to be considered? –  enzotib Jul 25 '12 at 18:33
    
You're right, one should consider them as well. –  A. Bellmunt Aug 2 '12 at 18:35
add comment

WLOG let $C$ be the largest angle, let $x=\frac{A-B}{2}, y=\frac{A+B}{2}$ then $-\frac{\pi}{4}<x<\frac{\pi}{4}, 0<y<\frac{\pi}{2}$. $$ A = x+y,~~ B=y-x,~~ C = \pi-2y \\ \cos\left(\frac{B-C}{2}\right) = \sin\left(\frac{3y-x}{2}\right), ~~ \cos\left(\frac{C-A}{2}\right) = \sin\left(\frac{3y+x}{2}\right) \\ \sin\left(\frac{3y-x}{2}\right)+\sin\left(\frac{3y+x}{2}\right) = 2\cos(x/2)\sin(3y/2) \\ \cos(x/2)\ge \cos x>\frac{1}{\sqrt{2}}, ~\sin(3y/2)>0 \Rightarrow 2\cos(x/2)\sin(3y/2)\ge2\cos x\sin(3y/2) $$

Then we can write $$ \begin{align} 3 \!&+\cos\left(\frac{A-B}{2}\right)+\cos\left(\frac{B-C}{2}\right)+\cos\left(\frac{C-A}{2}\right) -4(\cos A + \cos B + \cos C) \\ & = 3 + \cos x + 2\cos(x/2)\sin(3y/2)-4(\cos(x+y)+\cos(y-x)-\cos2y) \\ & = -1+\cos x+2\cos(x/2)\sin(3y/2)-8\cos x\cos y+8\cos^2y \\ & \ge 8\cos^2y-1+\cos x(1+2\sin(3y/2)-8\cos y) \\ & = 8\cos^2y-1+\cos x \cdot f(y) \end{align} $$ where we define $f(y)=1+2\sin(3y/2)-8\cos y$. Writing $v=y/2$ we can work through $$ \begin{align} 8\cos^2y-1+f(y) & = 7-8\sin^22v+1+2\sin3v-8\cos 2v\\ & = 8-16\sin^2v(1-2\sin^2v)+6\sin v-8\sin^3v-8(1-2\sin^2v) \\ & = 32\sin^4v-8\sin^3v-16\sin^2v+6\sin v \\ & = 2\sin v(1-2\sin v)^2(3+4\sin v) \end{align} $$ This last expression is clearly $\ge 0$ when $\sin v\ge 0$, but to answer the original question we now need to consider cases.

If $f(y)\le 0$, which corresponds to $0<y\le R=1.192797\cdots$ then $$ 8\cos^2y-1+\cos x\cdot f(y)\ge 8\cos^2y-1+f(y) \ge 0 $$ as we just described.

On the other hand if $R<y<\pi/2, ~f(y)>0$ then since $|x|<\pi/4$ $$ \begin{align} 8\cos^2y-1+\cos x\cdot f(y) & \ge 8\cos^2y-1+\frac{1}{\sqrt{2}}f(y)\\ & = 8\cos^2y-1+f(y)-f(y)\left(1-\frac{1}{\sqrt{2}}\right) \\ & = 2\sin v(1-2\sin v)^2(3+4\sin v)-f(y)\left(1-\frac{1}{\sqrt{2}}\right) \end{align} $$ I don't have an algebraic way to proceed from here, but it is easy to check numerically that the last expression is positive for $y$ in the desired range, which establishes the original inequality in $A,B,C$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.